The causal association between circulating cytokines with the risk of frailty and sarcopenia under the perspective of geroscience - Wang, Congzhi; Wang, Jiazhi; Wan, Rui; Kurihara, Hiroshi; Wang, Min (Frontiers in Endocrinology, 2024)
Introduction Circulating cytokines were considered to play a critical role in the initiation and propagation of sarcopenia and frailty from observational studies. This study aimed to find the casual association between circulating cytokines and sarcopenia and frailty from a genetic perspective by two-sample Mendelian randomization (MR) analysis. Methods Data for 41 circulating cytokines were extracted from the genome-wide association study dataset of 8,293 European participants. Inverse-variance weighted (IVW) method, MR-Egger, and weighted median method were applied to assess the relationship of circulating cytokines with the risk of aging-related syndromes and frailty. Furthermore, MR-Egger regression was used to indicate the directional pleiotropy, and Cochran’s Q test was used to verify the potential heterogeneity. The “leave-one-out” method was applied to visualize whether there was a causal relationship affected by only one anomalous single-nucleotide polymorphisms. Results Genetic predisposition to increasing levels of interleukin-10 (IL-10), IL-12, and vascular endothelial growth factor (VEGF) was associated with the higher risk of low hand grip strength according to the IVW method [R = 1.05, 95% CI = 1.01–1.10, P = 0.028, false discovery rate (FDR)–adjusted P = 1.000; OR = 1.03, 95% CI = 1.00–1.07, P = 0.042, FDR-adjusted P = 0.784; OR = 1.02, 95% CI = 1.00–1.05, P = 0.038, FDR-adjusted P = 0.567]. Furthermore, genetically determined higher macrophage colony-stimulating factors (M-CSFs) were associated with a lower presence of appendicular lean mass (OR = 1.01, 95% CI = 1.00–1.02, P = 0.003, FDR-adjusted P = 0.103). Monokine induced by interferon-γ (MIG) and tumor necrosis factor–beta (TNF-β) were associated with a higher risk of frailty (OR = 1.03, 95% CI = 1.01–1.05, P < 0.0001, FDR-adjusted P = 0.012; OR = 1.01, 95% CI = 1.00–1.03, P = 0.013, FDR-adjusted P = 0.259). In this study, we did not find heterogeneity and horizontal pleiotropy between the circulating cytokines and the risk of frailty and sarcopenia. Conclusion Genetic predisposition to assess IL-10, IL-12, and VEGF levels was associated with a higher risk of low hand grip strength and M-CSF with the presence of appendicular lean mass. The high levels of TNF-β and MIG were associated with a higher risk of frailty. More studies will be required to explore the molecular biological mechanisms underlying the action of inflammatory factors.